Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1104/pp.111.182436
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Legume Versus Nonlegume Tropical Tree Seedlings to Elevated CO2 Concentration  

Abstract: We investigated responses of growth, leaf gas exchange, carbon-isotope discrimination, and whole-plant water-use efficiency (W P ) to elevated CO 2 concentration ([CO 2 ]) in seedlings of five leguminous and five nonleguminous tropical tree species. Plants were grown at CO 2 partial pressures of 40 and 70 Pa. As a group, legumes did not differ from nonlegumes in growth response to elevated [CO 2 ]. The mean ratio of final plant dry mass at elevated to ambient [CO 2 ] (M E /M A ) was 1.32 and 1.24 for legumes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 65 publications
(74 reference statements)
10
65
0
4
Order By: Relevance
“…There was no positive response to increasing c a in either of the two angiosperm species. The lack of a growth response of Tabebuia and Chrysophyllum to c a is consistent with previous experiments in which seedlings of tropical tree species were grown in unfertilized soil (Lovelock et al, 1998;Winter et al, 2000;Cernusak et al, 2011). The causes of differential responses of plants to elevated c a in greenhouse experiments have recently been revisited by Ali et al (2013).…”
Section: Photosynthetic and Growth Responses To Variation In C Asupporting
confidence: 75%
See 1 more Smart Citation
“…There was no positive response to increasing c a in either of the two angiosperm species. The lack of a growth response of Tabebuia and Chrysophyllum to c a is consistent with previous experiments in which seedlings of tropical tree species were grown in unfertilized soil (Lovelock et al, 1998;Winter et al, 2000;Cernusak et al, 2011). The causes of differential responses of plants to elevated c a in greenhouse experiments have recently been revisited by Ali et al (2013).…”
Section: Photosynthetic and Growth Responses To Variation In C Asupporting
confidence: 75%
“…Both Tabebuia and Chrysophyllum have been used extensively in previous ecophysiological work in Panama (e.g. Cernusak et al, 2008Cernusak et al, , 2011. All four genera form arbuscular mycorrhizal associations (Dickie and Holdaway, 2010).…”
Section: Study Speciesmentioning
confidence: 99%
“…At the leaf level, g s typically declines in response to elevated c a (Wullschleger et al 2002;Ainsworth and Rogers 2007), although not always (Körner and Würth 1996;Keel et al 2007). Declining g s in response to elevated c a has been observed in seedlings and saplings of tropical tree species (Berryman et al 1994;Goodfellow et al 1997;Cernusak et al 2011b). An example of the response of g s to growth at elevated compared with ambient c a is shown in Fig.…”
Section: Effects Of Elevated C a On Leaf Gas Exchangementioning
confidence: 94%
“…Ormosia macrocalyx plays an important role in CO 2 uptake by the forest biomass, and the effect of carbon capture by forests provides an important opportunity in land management to increase the capacity of the soil to respond to disturbances that arise from the intense pressures of both land use and climate change (Banwart et al 2015). Cernusak et al (2011) found that O. macrocalyx can reach high nodulation rates (48.9 mg·g -1 ) on unfertilized soils and provided evidence for a positive relationship between N 2 fixation and nodule mass ratio, inferring that this tree has the highest rate of N 2 fixation relative to other leguminous species. They estimated the proportion of the plant N acquired by N 2 fixation to be about 84 %.…”
Section: Georgina Vargas-simónmentioning
confidence: 99%